Go with the flow: testing the effects of emotional flow on attitudinal and behavioral changes - Noland, Chris R. (Frontiers in Communication, 2025)
Emotions are important constructs that affect the lives of everyone. Emotions play a particularly strong role in persuasion. This study examines the concept of emotional flow, a sequencing of specific discrete emotions in a strategic manner to affect attitudes and behaviors. An experiment was conducted using a public service announcement about melanoma that contained a sequence that flowed from humor to sadness to hope in order to understand the functions and applicability of emotional flow, specifically within health contexts. Using Mood Management Theory and Excitation Transfer Theory as guides, results showed that participants who viewed a humor-sadness-hope emotional flow had higher levels of arousal compared to those who viewed humor-sadness or humor-sadness-neutral emotional flows. The humor-sadness-hope emotional flow resulted in higher levels of pleasure compared to those who viewed the humor-sadness emotional flow. Arousal was identified as a mediator between emotional flow and both message engagement and risk perceptions. Additionally, sadness was found to moderate the relationship between emotional flow and both attitude and message engagement. Theoretical and practical implications highlight the role that sequential emotions can play in increasing emotional intensity and the importance for companies to recognize this role and plan their messaging accordingly.